2009
DOI: 10.1001/archsurg.2008.547
|View full text |Cite
|
Sign up to set email alerts
|

Arterial and Venous Resection for Pancreatic Adenocarcinoma

Abstract: In this combined experience, en bloc vascular resection consisting of venous resection alone, arterial resection alone, or combined vascular resection at the time of pancreatectomy for adenocarcinoma did not adversely affect postoperative mortality, morbidity, or overall survival. The need for vascular resection should not be a contraindication to surgical resection in the selected patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(117 citation statements)
references
References 19 publications
(26 reference statements)
3
110
0
4
Order By: Relevance
“…By excluding the first series with regional pancreatectomy, vein resection does not have prognostic significance regarding the survival. Large series with radical surgical resection showed that surgical morbidity and mortality rates are comparable to standard pancreatic head resections [38][39][40]. Comparable complication rates between standard pancreaticoduodenectomy (PD) and pancreaticoduodenectomy with vascular resection (PDVR) were reported by some studies [12,13].…”
Section: Outcomementioning
confidence: 98%
“…By excluding the first series with regional pancreatectomy, vein resection does not have prognostic significance regarding the survival. Large series with radical surgical resection showed that surgical morbidity and mortality rates are comparable to standard pancreatic head resections [38][39][40]. Comparable complication rates between standard pancreaticoduodenectomy (PD) and pancreaticoduodenectomy with vascular resection (PDVR) were reported by some studies [12,13].…”
Section: Outcomementioning
confidence: 98%
“…Studies from high-volume centers, containing selected patients have shown similar morbidity, mortality, and survival rates if a margin-negative resection was performed [79][80][81]. A systematic review concluded that venous resection is a safe and feasible procedure that increases the number of patients who can undergo curative resection and, therefore, may provide important survival benefits to selected groups of patients [82].…”
Section: Vascular Resectionmentioning
confidence: 99%
“…Highvolume centers, with expertise in en bloc resection of the hepatic artery, superior mesenteric artery, or even the celiac trunk itself [86][87][88] have shown good survival outcomes.…”
Section: Vascular Resectionmentioning
confidence: 99%
“…Thus, a small portion of portal vein encroachment may be considered resectable in most, but not all centres dealing with these cancers [40,41]. However, arterial involvement is considered operable only by a minority of the centres of excellence and, even in those series of patients, the peri-operative outcome is not good [41,42].…”
Section: Post-test Variabilitymentioning
confidence: 99%